Sycophancy as a Pathology of Political Communication in Indonesia: A Critical Discourse Analysis - kiki esa perdana (Jurnal Komunikasi Dialogis, 2026)
Abstract - This study examines sycophancy as a pervasive pathology in contemporary Indonesian political communication. Employing a Critical Discourse Analysis (CDA) approach, we analyze how political actors construct discourses of absolute loyalty and excessive praise to build and sustain power. Drawing on data from political speeches, media coverage, and social media interactions during the 2019–2024 period, the research reveals that sycophantic discourse systematically erodes public accountability, suppresses substantive policy debate, and perpetuates a deeply entrenched patronage culture. The findings demonstrate that sycophancy transforms political communication from a deliberative tool into a ritual of power consolidation, thereby undermining democratic quality. This study contributes to theoretical understanding by showing how informal cultural practices—rooted in feudal and colonial legacies—are formalized into pathological political discourse. The article concludes with recommendations for strengthening democratic resilience and promoting critical public dialogue in Indonesia.